PERAN PEDAGANG LOKAL DALAM PEMASARAN OBAT HERBAL BAJAKAH JATI DI PASAR KAHAYAN PALANGKA RAYA: The Role Of Local Traders In Marketing Bajakah Jati Herbal Medicine At Kahayan Market, Palangka Raya - Qiftiyah, Ulfatul; Pratama, Reksa; Agustin, Yul; Setyanto, Zola Ari (Ganec Swara, 2025)
This research discusses the role of local traders in marketing Bajakah herbal medicine at the Kahayan Market in Palangka Raya, Central Kalimantan. Bajakah (Spatholobus littoralis Hassk.) is a typical Kalimantan plant which has health benefits and has long been used by the Dayak people as traditional medicine. This research aims to find out how local traders play a role in introducing, promoting and maintaining consumer trust in Bajakah herbal products. The research method used is descriptive qualitative through observation, interviews and documentation of traders and consumers at the Bajakah Jati Herbal Shop. The research results show that local traders play a role not only as sellers, but also as promoters, educators and liaisons between producers and consumers. The marketing strategy is carried out through direct sales and simple, trust-based promotions using social media such as WhatsApp and Facebook. The main obstacles faced include limited digital promotion, lack of product legality, and dependence on forest products for raw materials. However, the increasing trend of natural lifestyles opens up great opportunities for the development of local herbal products. With the support of training, packaging innovation and official legality, local traders have the potential to expand the market and contribute to the regional economy and preserve local wisdom.